(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Assessing anxiety, depression, malnutrition, and associated factors in cancer patients. Method: A cross-sectional study was conduced on 118 cancer patients at Oncology Department, Hue University of Medicine and Pharmacy Hospital. We assessed nutritional status based on Global Leadership Initiative on Malnutrition (GLIM). Additionally, Hospital Anxiety and Depression Scale (HADS) was used to screen patients with anxiety and depression. Results: A total of 32.2% of patients were classified as malnourished based on GLIM. Additionally, 9.3% and 16.1% of patients were found to have anxiety and depression, respectively. Notably, depression was significantly associated with malnutrition (OR = 4.255; 95% CI: 1.527-11.855). Conclusion: Malnutrition, anxiety, and depression are commonly recognized problems in cancer patients and are often interrelated. Study highlights the importance of screening for both malnutrition and mental health issues at the time of diagnosis.